2017
DOI: 10.1002/mrc.4605
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR study of the phase behavior of aqueous eutectic solutions using the inverse Laplace transform analysis of T2 relaxation

Abstract: High-field H NMR T relaxation studies were used to characterize the changes in the physical phases of water, NaCl, and dextrose solutions over a temperature range of -65 to 15 °C. The data were analyzed with the inverse Laplace transform and with a linear fit to the logarithm of the time domain signal. Two liquid phases were detected for the NaCl and dextrose solutions at lower temperatures and assigned to low and high concentrated solution domains. The high concentrated solution domain was found to be present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…8-10 A few studies have been reported in the literature, wherein the hydrogen bonding interactions of deep eutectic solvents (DESs) were determined by MAS solid-state NMR techniques. [11][12][13][14] Mann et al reported a study in which 1 H-1 H NOESY and ROESY MAS NMR were used for the identification of specific hydrogen bonding interactions in a DES system of lidocaine and ibuprofen. 11 Agostino et al reported the use of 23 Na NMR T 1 relaxation measurements for understanding the diffusion and dynamics of sodium ions in salt-glycerol DES mixtures.…”
mentioning
confidence: 99%
“…8-10 A few studies have been reported in the literature, wherein the hydrogen bonding interactions of deep eutectic solvents (DESs) were determined by MAS solid-state NMR techniques. [11][12][13][14] Mann et al reported a study in which 1 H-1 H NOESY and ROESY MAS NMR were used for the identification of specific hydrogen bonding interactions in a DES system of lidocaine and ibuprofen. 11 Agostino et al reported the use of 23 Na NMR T 1 relaxation measurements for understanding the diffusion and dynamics of sodium ions in salt-glycerol DES mixtures.…”
mentioning
confidence: 99%